Matrix-bound nanovesicles within ECM bioscaffolds - Huleihel, Luai (Sci Adv, 2016)
Biologic scaffold materials composed of extracellular matrix (ECM) have been used in a variety of surgical and tissue engineering/regenerative medicine applications and are associated with favorable constructive remodeling properties including angiogenesis, stem cell recruitment, and modulation of macrophage phenotype toward an anti-inflammatory effector cell type. However, the mechanisms by which these events are mediated are largely unknown. Matrix-bound nanovesicles (MBVs) are identified as an integral and functional component of ECM bioscaffolds. Extracellular vesicles (EVs) are potent vehicles of intercellular communication due to their ability to transfer RNA, proteins, enzymes, and lipids, thereby affecting physiologic and pathologic processes. Formerly identified exclusively in biologic fluids, the presence of EVs within the ECM of connective tissue has not been reported. In both laboratory-produced and commercially available biologic scaffolds, MBVs can be separated from the matrix only after enzymatic digestion of the ECM scaffold material, a temporal sequence similar to the functional activity attributed to implanted bioscaffolds during and following their degradation when used in clinical applications. The present study shows that MBVs contain microRNA capable of exerting phenotypical and functional effects on macrophage activation and neuroblastoma cell differentiation. The identification of MBVs embedded within the ECM of biologic scaffolds provides mechanistic insights not only into the inductive properties of ECM bioscaffolds but also into the regulation of tissue homeostasis.